2018
DOI: 10.1007/s00109-018-1710-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α regulation of myeloid cells

Abstract: Hematopoietic myeloblasts give rise to macrophages, dendritic cells, and neutrophils. Circulating myeloid cells detect invading microbes using pattern recognition receptors and subsequently orchestrate an innate immune response to contain and kill the pathogens. This innate immune response establishes an inflammatory niche characterized by hypoxia due to host and pathogen factors. Hypoxia-inducible factor (HIF) transcription factors are the primary regulators of the myeloid response to hypoxia. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 133 publications
(158 reference statements)
0
20
0
Order By: Relevance
“…This has been shown to be dependent on a shift from oxidative phosphorylation toward glycolysis through an Akt/mTOR/HIF-1α dependent pathway (183,186). We recently reviewed regulation and function of HIF-1α in myeloid cells (187). On the other hand, TLR ligands (such as LPS, MPLA, and CPG) increase aerobic glycolysis in concert with increased antimicrobial functions (such as respiratory burst and phagocytosis) as well as induce mitochondrial biogenesis and increased oxidative metabolism (47).…”
Section: Metabolic Reprogramming and Innate Immune Memorymentioning
confidence: 99%
“…This has been shown to be dependent on a shift from oxidative phosphorylation toward glycolysis through an Akt/mTOR/HIF-1α dependent pathway (183,186). We recently reviewed regulation and function of HIF-1α in myeloid cells (187). On the other hand, TLR ligands (such as LPS, MPLA, and CPG) increase aerobic glycolysis in concert with increased antimicrobial functions (such as respiratory burst and phagocytosis) as well as induce mitochondrial biogenesis and increased oxidative metabolism (47).…”
Section: Metabolic Reprogramming and Innate Immune Memorymentioning
confidence: 99%
“…Just as succinate stabilizes HIF, also other metabolites, such as fumarate, pyruvate, and lactate, can inhibit PHD resulting in HIF stabilization . The upregulation of glycolysis by HIF1α and subsequent activation of HIF1α by glycolytic enzymes and TCA intermediates creates a positive feedback loop that drives macrophages to produce IL1β and ROS resulting in eradication of the invading pathogens .…”
Section: Crosstalk Between Hif and Sepsismentioning
confidence: 99%
“…For an extensive review on the role of HIF1α in myeloid cells, we refer to the recent review of Stothers et al . . Here, we will discuss briefly the role of HIF1α in monocyte, neutrophil, and DC function.…”
Section: Crosstalk Between Hif and Sepsismentioning
confidence: 99%
“…Since activation of immune cells under normoxic conditions already triggers a switch to glycolytic energy generation, these cells are well prepared to operate in inflamed areas, which are very likely to display low oxygen levels. The hypoxia-inducible factor (HIF) plays an important role not only for the adaptation of cells to oxygen-poor environments (reviewed: [49,50]), but also under normoxic conditions (reviewed: [39,42,[44][45][46]51]). Therefore, we will very briefly review the molecular mechanisms that result in HIF stabilization in myeloid cells and we will describe the role of HIF in the immunobiology of neutrophils, macrophages, and dendritic cells.…”
Section: Metabolic Response Of Innate Immune Cells To Hypoxiamentioning
confidence: 99%
“…In the absence of oxygen, its co-substrate or co-factors, the PHD activity is suppressed, which in turn triggers subsequent HIF1α activation (reviewed: [49,50,52,61]). HIFα governs the expression of a plethora of different genes involved in metabolism, immune system regulation, and in general cellular functions in response to hypoxia (reviewed: [39,42,[44][45][46]51]). A detailed global assessment of HIF1α and HIF2α binding sites in MCF7 breast cancer cells, for instance, revealed that many of these sites bound HIF1α and HIF2α equally well, while there were only very few sites that bound HIF2α exclusively [62].…”
Section: Hypoxic Hif Stabilizationmentioning
confidence: 99%